2005
DOI: 10.1186/1550-2783-2-2-4
|View full text |Cite
|
Sign up to set email alerts
|

Obesity: Prevalence, Theories, Medical Consequences, Management, and Research Directions

Abstract: Obesity and its associated disorders are a growing epidemic across the world. Many genetic, physiological, and behavioral factors play a role in the etiology of obesity. Diet and exercise are known to play a valuable role in the treatment and prevention of obesity and associated disorders such as hypertension, heart disease, and diabetes. Therefore, the purpose of this review is to examine the prevalence, etiology, consequences, and treatment of obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
150
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(171 citation statements)
references
References 189 publications
5
150
0
2
Order By: Relevance
“…Previously, fats were supposed to play a leading role induce obesity because of including high-calorie, unlike this, some studies have been done about the carbohydrates induce obesity in recent years (1)(2)(3). According to Dr. Atkins trigger of obesity on foods are not fat and proteins, but carbohydrates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, fats were supposed to play a leading role induce obesity because of including high-calorie, unlike this, some studies have been done about the carbohydrates induce obesity in recent years (1)(2)(3). According to Dr. Atkins trigger of obesity on foods are not fat and proteins, but carbohydrates.…”
Section: Introductionmentioning
confidence: 99%
“…According to Dr. Atkins trigger of obesity on foods are not fat and proteins, but carbohydrates. In Dr. Atkins diet method, daily carbohydrate intake is limited with maximum 20 grams protein and no restrictions are imposed on proteins and fats (1).…”
Section: Introductionmentioning
confidence: 99%
“…It is known that obesity is related to impairments in lipid metabolism 26 . A research work by Coelho et al 27 in 153 medicine students (18 to 31 years old) revealed high levels of CT and TG only in obese individuals.…”
Section: Discussionmentioning
confidence: 99%
“…[49][50][51][52][53][54][55][56][57][58][59][60]. It is critical to understand that even with the most unfortunate genetic composition that predisposes an individual to metabolic disease [61], such as the well documented US Pima Indians with the world's highest prevalence of type 2 diabetes (38%), that physical activity (energy expenditure) and diet can have a profound effect on upon prevention.…”
Section: Animal Models With Dermis Issuesmentioning
confidence: 99%